2013
DOI: 10.12966/psbr.10.04.2013
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Relationships in the Primary Classroom: An Analysis of Social and Affective Outcomes

Abstract: -Recent research regarding the quality of relationships in primary classrooms has focused largely on the enhancement and development of cognitive skills. The study reported here focused on a range of social and affective outcomes with the intention of broadening our understanding of the classroom as an interactive system, from the child's perspective. This paper provides empirical evidence on children's perceptions at Key Stage 2 (pupil age 7-11 years) of their relationships with teachers, other adults and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The study concluded that, as teachers develop through their career, there are areas of tension which may have an impact on their future relationships with pupils. A subsequent study [5] found that teacher-pupil relationships evident in primary classrooms contribute to the overall learning environment particularly in relation to interactions, routines, and activities. In addition, there was found to be a statistical association between pupils' views of their relationships with teachers and their self-reported satisfaction with school.…”
Section: Introductionmentioning
confidence: 96%
“…The study concluded that, as teachers develop through their career, there are areas of tension which may have an impact on their future relationships with pupils. A subsequent study [5] found that teacher-pupil relationships evident in primary classrooms contribute to the overall learning environment particularly in relation to interactions, routines, and activities. In addition, there was found to be a statistical association between pupils' views of their relationships with teachers and their self-reported satisfaction with school.…”
Section: Introductionmentioning
confidence: 96%